Stress-strain state of the flat-valgus foot model in case of implants usage for subtalar arthrorisis - Korolkov, Oleksandr; Rakhman, Paviel; Karpinsky, Mykhaylo; Shishka, Igor; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The flat-valgus foot deformity is one of the most common pathologies of the bone-joints system. flat-valgus foot deformity leads to the development of hallux valgus, excessive torsion of the crus, valgus deformation at the ankle and knee joints. Objective: to analyze the stress-strain state of the foot elements in the case of the results of experimental lumbar posterior-lateral fusion with platelet rich fibrin and after its correction with screws for subtalar arthroris. Methods: a biomechanical (mathematical) study was made with the finite element method on the foot model in normal and with The results of experimental lumbar posterior-lateral fusion with platelet rich fibrin. We performed subtalar arthroris with corrective screws, implanted into the calcaneus or talus bones. Results: in case of the results of experimental lumbar posterior-lateral fusion with platelet rich fibrin increases the level of stress in all the elements of its bone model, especially on the supporting surfaces of the calcaneus and the surfaces of subtalar joint. At screws fixation there are two areas of high stresses (in the contact of the bone elements of the model with screws) with absolute values exceeding the parameters of the model with the results of experimental lumbar posterior-lateral fusion with platelet rich fibrin. Strain distribution was almost equal in cases of screw implantation in the calcaneus or talus bones. The highest stresses in the talus (12.5 MPa) were lower in the model with screws implanted into the calcaneus (11.1 МПа), so this option can be considered to be better. Conclusions: usage of screw for subtalar arthrorisis allows to reduce stresses compared to the model with implants for arthroeresis, with the exception of contact points of bone with screws.